Traditional Knowledge for Sustainable Development: A Case from the Health Sector in Kerala, India - Unnikrishnan P AYYAPPALLIMANA and Osamu KOIKE
The United Nations’ Decade of Education for Sustainable Development (DESD) aims, among other objectives, to foster and promote the mainstreaming of intercultural approaches within a social learning process through multi-sectoral, collaborative and interdisciplinary methods. Biological as well as cultural diversity are inherently linked and form an important part of the sustainable development education process. Traditional knowledge (TK), a central dimension of bio-cultural diversity, is also receiving increased attention in this context. However there are several socio-political and methodological challenges of integrating TK in Education for Sustainable Development (ESD) programs. Using the case of traditional medicine from Kerala state, India, this paper attempts to highlight the importance of and the issues pertinent to such integration in a local context. It also highlights the role of endogenous development processes to achieve different objectives, including specifically those related to ESD processes. Appropriate learning methods need to be designed with sensitivity to epistemological and contextual dimensions of traditional knowledge. For education programs to be effective they need to be addressed at various levels of social integration such as communities, civil society groups, nongovernmental organizations, formal and informal learning institutions, local administrative structures, and national, international, multilateral and policy forums.